Guiding future research on psychological interventions in people with COVID-19 and post COVID syndrome and comorbid emotional disorders based on a systematic review - Martínez-Borba, Verónica; Martínez-García, Laura; Peris-Baquero, Óscar; Osma, Jorge; del Corral-Beamonte, Esther (Frontiers in Public Health, 2024)
Objective: The COVID-19 pandemic has been emotionally challenging for the entire population and especially for people who contracted the illness. This systematic review summarizes psychological interventions implemented in COVID-19 and long COVID-19 patients who presented comorbid emotional disorders. Methods and measures: 3839 articles were identified in 6 databases and 43 of them were included in this work. Two independent researchers selected the articles and assessed their quality. Results: 2359 adults were included in this review. Severity of COVID-19 symptoms ranged from asymptomatic to hospitalized patients; only 3 studies included long COVID-19 populations. Similar number of randomized controlled studies (n=15) and case studies (n=14) were found. Emotional disorders were anxiety and/or depressive symptoms (n=39) and the psychological intervention most represented had a cognitive behavioural approach (n=10). Length of psychological programs ranged from 1-5 sessions (n=6) to 16 appointments (n=2). Some programs were distributed on a daily (n=4) or weekly basis (n=2), but other proposed several sessions a week (n=4). Short (5-10 minutes, n=4) and long sessions (60-90 minutes, n=3) are proposed. Most interventions were supported by the use of technologies (n=18). Important risk of bias was present in several studies. Conclusion: promising results in the reduction of depressive, anxiety and related disorders have been found. However, important limitations in current psychological interventions were detected (i.e., duration, format, length, and efficacy of interventions were not consistently established across investigations). The results derived from our work may help to understand clinical practices in the context of pandemics and could guide future efforts to manage emotional suffering in COVID-19 patients. A stepped model of care could help to determine the dosage, length and format of delivery for each patient.